Sikap Dokter Puskesmas di Jakarta Terhadap Pasien dengan Adiksi Zat Psikoaktif - Fajar Pranoto (Bahasa Indonesia, 2021)
Introduction: The increasing number of substance use cases has been becoming a public health problem in Indonesia. Primary healthcare doctors play an important role in health promotion and early detection of health problems. Several studies have shown that, physicians have negative attitudes towards patients with substance use problem. Negative attitudes among physicians may affect the quality of healthcare delivery. The objective of the current study was to assess primary healthcare doctors’s attitudes towards patients with substance use problems in Jakarta. Methods: This was an observational descriptive study using a cross-sectional method. Participants of this research were primary healthcare doctors in Jakarta. Data were gathered using Medical Condition Regard Scale. Participants’ attitudes towards patients with substance use problems was analysed using a descriptive approach. Result: 569 data from participants were analysed. Most of them were female, age 25-35 years old, and have less than 5 years working experience. We found that 307 primary healthcare doctors had negative attitudes toward patients with substance use problems (54%) and 262 doctors had positive attitudes (46%). Conclusion: The result indicates that primary healthcare doctors in Jakarta have negative attitudes towards patients with substance use problems. Further studies are needed to evaluate factors that might influence such attitude. Keywords: attitudes, primary healthcare doctors, Medical Condition Regard Scale